Standard Operating Procedures (SOPs) for Institutional Biosafety Committees - Uganda National Council for Science and Technology (Uganda National Council for Science and Technology, 2021)
The Standard Operating Procedures (SOPs) for Institutional Biosafety Committees (IBCs) in Uganda provide a comprehensive framework for the establishment, registration, governance, and operation of Institutional Biosafety Committees within organizations conducting bioscience research and development involving genetically modified organisms (GMOs), recombinant DNA (rDNA), infectious agents, and other hazardous biological materials. The SOPs are intended to complement Uganda's existing biosafety policies, legislation, and international obligations under the Cartagena Protocol on Biosafety. They define the mandate, composition, functions, and responsibilities of IBCs and Biological Safety Officers, while outlining procedures for the review and approval of research applications, laboratory and field inspections, risk assessment, emergency response, reporting, record management, training, and performance assessment. The document also establishes mechanisms for coordination between research institutions and the Uganda National Council for Science and Technology (UNCST) to ensure compliance with national biosafety requirements, safeguard human health and the environment, and promote responsible conduct of biotechnology research in Uganda.
Keywords: Standard Operating Procedures (SOPs) for Institutional; Biosafety Committees; Uganda